STEM EDUCATIONFOR VOCATIONAL STUDENTS - เสือคง ธิดารัตน์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
This research aimed to study the management of STEM education and opinion of students for vocational certificate students in science – based school projects in College of Agriculture and Technology Lamphun. The data was collected from 96 participants.The opinion of STEM education from eighty-three students were collected by questionnaires.The field note was collected by interview from thirteen teachers. The statistical data used this research were, percentage, mean and standard deviation. The result of this study were revealed as follow: 1. Learning management of STEM education for vocational certificate students in science – based school projects has cooperation in manage curriculum with as 1) College of Agriculture and Technology Lamphun 2) Vocational Education Commission cooperate British Council and Newton Fund 3) Rajamangala University of Technology Lanna. According to learning management from 3 cooperates , the students have chance to practice and it enhance the creative thinking process, collaborative process the students label apply in everyday life. 2. The opinion of students had towards learning management of STEM overall was in high level ( =3.61). When specifically considered within each aspect, 3 aspects were in the high level, 1 aspect was in the moderate level. When ranking all aspects, the highest mean was learning activity, The second was And the third was educational aid.